Adult Education Teachers’ Competencies for the Implementation of Sustainable Development - Siniša Kušić; Renata Hasel (AS: Andragoška Spoznanja)
This paper presents the results of a study conducted on a sample of teachers working in adult education in Croatia with the aim of determining whether they possess the competencies needed for the implementation of sustainable development in the teaching process. The results show that the teachers who participated in the study mostly expressed positive attitudes but lower levels of both knowledge about sustainable development concepts and education for it. Even though teachers on average self-evaluated that they possessed almost every generic and specific competency needed for sustainable development, their self-evaluation also shows that they only partially possess the competencies directly connected with the implementation of sustainable development in the adult education teaching process.